Military Surgical Team Communication: Implications for Safety. Issue 3 (28th October 2019) - Stucky, Christopher H; De Jong, Marla J; Kabo, Felichism W
Abstract: Introduction: Medical error is the third leading cause of death in the United States, contributing to suboptimal care, serious patient injury, and mortality among beneficiaries in the Military Health System. Recent media reports have scrutinized the safety and quality of military healthcare, including surgical complications, infection rates, clinician competence, and a reluctance of leaders to investigate operational processes. Military leaders have aggressively committed to a continuous cycle of process improvement and a culture of safety with the goal to transform the Military Health System into a high-reliability organization. The cornerstone of patient safety is effective clinician communication. Military surgical teams are particularly susceptible to communication error because of potential barriers created by military rank, clinical specialty, and military culture. With an operations tempo requiring the military to continually deploy small, agile surgical teams, effective interpersonal communication among these team members is vital to providing life-saving care on the battlefield. Methods: The purpose of our exploratory, prospective, cross-sectional study was to examine the association between social distance and interpersonal communication in a military surgical setting. Using social network analysis to map the relationships and structure of interpersonal relations, we developed six networks (interaction frequency, close working relationship, socialization, advice-seeking, advice-giving, and speaking-up/voice) and two models that represented communication effectiveness ratings for each participant. We used the geodesic or network distance as a predictor of team member network position and assessed the relationship of distance to pairwise communication effectiveness with permutation-based quadratic assignment procedures. We hypothesized that the shorter the network geodesic distance between two individuals, the smaller the difference between their communication effectiveness. Results: We administered a network survey to 50 surgical teams comprised of 45 multidisciplinary clinicians with 522 dyadic relationships. There were significant and positive correlations between differences in communication effectiveness and geodesic distances across all five networks for both general ( r = 0.819–0.894, P < 0.001 for all correlations) and task-specific ( r = 0.729–0.834, P < 0.001 for all correlations) communication. This suggests that a closer network ties between individuals is associated with smaller differences in communication effectiveness. In the quadratic assignment procedures regression model, geodesic distance predicted task-specific communication ( β = 0.056–0.163, P < 0.001 for all networks). Interaction frequency, socialization, and advice-giving had the largest effect on task-specific communication difference. We did not uncover authority gradients that affect speaking-up patterns among surgical clinicians. Conclusions: The findings have important implications for safety and quality. Stronger connections in the interaction frequency, close working relationship, socialization, and advice networks were associated with smaller differences in communication effectiveness. The ability of team members to communicate clinical information effectively is essential to building a culture of safety and is vital to progress towards high-reliability. The military faces distinct communication challenges because of policies to rotate personnel, the presence of a clear rank structure, and antifraternization regulations. Despite these challenges, overall communication effectiveness in military teams will likely improve by maintaining team consistency, fostering team cohesion, and allowing for frequent interaction both inside and outside of the work environment.